Kontekstualisasi ‘Uzlah Pada Q.S Al-Kahf Ayat 16 Perspektif Sayyid Quṭb Dalam Tafsir Fī Ẓilāl Al-Qur'ān - Syafira Rahmadhana; Nur Ikhlas; Muhammad Lazim (PT. Student Rihlah Indonesia, 2026)
Amid the rapid development of globalization and digital technology, many Muslims face various challenges in maintaining their spiritual quality and the integrity of their faith. In this context, the concept of ‘uzlah has become an important subject of study as an effort to protect oneself from influences that may negatively affect religious life. This research aims to analyze the meaning of ‘uzlah in Q.S. Al-Kahf [18]:16 according to Sayyid Quṭb through Abdullah Saeed’s contextual hermeneutical approach and to identify its relevance in contemporary life. This study employs a qualitative library research method, using Tafsir Fī Ẓilāl Al-Qur'ān as the primary source and analyzing the data through Abdullah Saeed’s theory of contextual hermeneutics. The findings indicate that ‘uzlah, from Sayyid Quṭb’s perspective, does not merely signify physical isolation but also encompasses theological, social, and spiritual dimensions as a means of safeguarding one’s faith from environmental influences that may undermine religious commitment. Through Abdullah Saeed’s hierarchy of values framework, the protection of faith is understood as a fundamental and universal value, while its practical implementation remains contextual.In the modern context, the values of ‘uzlah can be actualized through the management of social interactions, the wise use of technology, the strengthening of worship, and engagement in reflective and spiritual practices. These findings demonstrate that ‘uzlah remains relevant as an ethical and spiritual principle for addressing the challenges of contemporary life without necessarily requiring physical withdrawal from society.